2017
DOI: 10.1097/mib.0000000000001002
|View full text |Cite
|
Sign up to set email alerts
|

Premedication Use Before Infliximab Administration

Abstract: Background Premedications are commonly given to inflammatory bowel disease (IBD) patients prior to intravenous infliximab administration. We aimed to (1) describe practice variability; and (2) determine clinician rationale for premedicating IBD patients prior to infliximab administration. Methods We developed a cross-sectional electronic survey after comprehensive literature review to assess practice variability and clinician rationale for premedication use prior to infliximab. An optional post-survey quiz a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
(33 reference statements)
2
15
0
Order By: Relevance
“…Only 20% did not routinely use premedications and 18% identified the potential association of diphenhydramine use with increased reactions. 9 Previous data have suggested that administration of antihistamines, alone or in combination with corticosteroids and/or antipyretics, might be paradoxically associated with higher rates of immediate IRs. 10,11 This finding is obviously discordant from our findings; however, this difference again could be related to possible selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…Only 20% did not routinely use premedications and 18% identified the potential association of diphenhydramine use with increased reactions. 9 Previous data have suggested that administration of antihistamines, alone or in combination with corticosteroids and/or antipyretics, might be paradoxically associated with higher rates of immediate IRs. 10,11 This finding is obviously discordant from our findings; however, this difference again could be related to possible selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…All the patients in our study were given pretreatment routinely with intravenous corticosteroids before each IFX infusion. However, high inter-practice and intra-practice variability for premedication use exits before IFX administration in different centers in Western countries [21]. The clinical rationale for premedicating patients seems to be driven by individual preference or group practice habit [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, high inter-practice and intra-practice variability for premedication use exits before IFX administration in different centers in Western countries [21]. The clinical rationale for premedicating patients seems to be driven by individual preference or group practice habit [21]. In contrast, data from the Mayo Clinic found that in the adult population, premedication was not associated with a reduced risk of recurrent IR [15].…”
Section: Discussionmentioning
confidence: 99%
“…Methylprednisolone has been given as a pre-infusion prophylaxis corticosteroid prior to the administration of other infusion biologic therapies, including infliximab and rituximab [7]. While hydrocortisone remains widely used by rheumatology practices as a pre-infusion prophylaxis for pegloticase, some providers use methylprednisolone as an alternative corticosteroid.…”
Section: Introductionmentioning
confidence: 99%